High-temperature-resistant battery diaphragm and preparation method thereof
By using titanium mixed benzozole to modify the metal organic skeleton and phenol -containing hydroxide polyetheric amine and other materials to prepare battery septum, and add specific nanoparticles and fibers to its surface The problem of melting significantly improves the high temperature resistance and safety performance of the diaphragm.
Patent Information
- Application Number
- CN202411576010.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-06
AI Technical Summary
Existing battery separators are prone to thermal shrinkage, melting or even burning in high temperature environments, threatening the safety of the battery system.
Use titanium doped pyramazole to modify the metal organic skeleton and phenol -containing polyetheric amine, prepare polyetheride amine septum through spinning technology, and add AL2O3@ZRO2 nuclear shell structure to the surface Acidal fiber forms a nuclear shell structure nanoparticles and fiber network structures.
It significantly improves the high temperature resistance of the battery diaphragm, suppresss heat contraction, maintains size stability and mechanical properties, and enhances the safety performance and cycle stability of the battery.
Smart Images

Figure CN119381692A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery separator preparation, and in particular to a high temperature resistant battery separator and a preparation method thereof. Background Art
[0002] With the transformation of the global energy structure and the rapid development of portable electronic devices, electric vehicles and other fields, the demand for lithium-ion batteries is growing. The safety, energy density and operating temperature range of batteries have become key factors restricting their widespread application. As one of the core components of lithium-ion batteries, battery separators not only directly affect the stability of the internal structure of the battery, but also are related to the safety performance and service life of the battery.
[0003] Currently, most battery separator materials on the market are made of polyolefin polymers, such as polypropylene (PP) and polyethylene (PE), which are widely used due to their excellent mechanical strength and good permeability. However, these materials have significant defects, especially in high temperature environments. When the internal temperature of the battery rises abnormally during rapid charging, overcharging or short circuit, the polyolefin separator is prone to thermal shrinkage, melting or even combustion, which seriously threatens the safety of the battery system.
[0004] Therefore, we proposed a high temperature resistant battery separator and a preparation method thereof. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a high temperature resistant battery separator and a preparation method thereof.
[0006] A method for preparing a high temperature resistant battery separator comprises the following steps: S1: Preparation of titanium-doped benzimidazole-modified metal-organic frameworks Zinc nitrate hexahydrate and 2-methylbenzimidazole are used as raw materials, and tetrabutyl titanate and 2-aminobenzimidazole are added to prepare a titanium-doped benzimidazole-modified metal organic framework; S2: Preparation of polyetherimide containing phenolic hydroxyl groups The polyetherimide containing phenolic hydroxyl group was prepared by using bis(3-amino-4-hydroxyphenyl)propane and 4,4-biphenyl ether dianhydride as raw materials. S3: Preparation of polyetherimide separator The titanium-doped benzimidazole-modified metal organic framework is added to a solution of phenolic hydroxyl-containing polyetherimide and N,N-dimethylformamide, followed by spinning to obtain a polyetherimide diaphragm; S4: Preparation of core-shell nanoparticles Al2O3@ZrO2 core-shell structure nanoparticles were prepared using zirconium dioxide, aluminum sulfate 18hydrate and ammonium formate as raw materials. S5: Preparation of barium titanate fibers Barium titanate fiber was prepared using barium hydroxide octahydrate, acetic acid and tetrabutyl titanate as raw materials. S6: Preparation of battery separators Barium titanate fibers and Al2O3@ZrO2 core-shell structured nanoparticles are used as additives to prepare a diaphragm coating, and the diaphragm coating is coated on the surface of a polyetherimide diaphragm to prepare a battery diaphragm.
[0007] Furthermore, step S1 of preparing titanium-doped benzimidazole-modified metal organic framework specifically comprises the following steps: S1.1: dissolving 2-3 parts by weight of zinc nitrate hexahydrate and 0.05-0.08 parts by weight of tetrabutyl titanate in 240-250 parts by weight of methanol, performing ultrasonication for 20-30 minutes, then adding 1-2 parts by weight of 2-methylbenzimidazole, stirring and mixing to obtain a mixed solution; S1.2: Add 5-8 parts by weight of 2-aminobenzimidazole to 50-60 parts by weight of methanol, stir and dissolve to obtain a 2-aminobenzimidazole methanol solution; S1.3: Slowly pour 1-2 parts by weight of the mixed solution into 1-2 parts by weight of 2-aminobenzimidazole methanol solution, and react for 4-5 hours under magnetic stirring, then centrifuge, wash the precipitate with methanol 2-3 times, and then dry to obtain a titanium-doped benzimidazole-modified metal organic framework.
[0008] Furthermore, step S2 of preparing the phenolic hydroxyl-containing polyetherimide specifically comprises the following steps: S2.1: In a nitrogen atmosphere, 1-2 parts by weight of bis(3-amino-4-hydroxyphenyl)propane and 15-18 parts by weight of N,N-dimethylacetamide are mixed in an ice bath, and magnetic stirring is performed until they are completely dissolved, and then 0.4-0.5 parts by weight of 4,4-biphenyl ether dianhydride powder is added, and stirring is continued for 20-30 minutes, and then 0.4-0.5 parts by weight of 4,4-biphenyl ether dianhydride powder is added, and stirring is continued for 20-30 minutes, and then 0.4-0.5 parts by weight of 4,4-biphenyl ether dianhydride powder is added, and stirring is continued for 5-6 hours to obtain a viscous polyamic acid solution; S2.2: Casting the viscous polyamic acid solution on a dust-free flat glass, heating it on a heating table, first heating it to 100-120°C, keeping it warm for 2-3 hours, then heating it to 150-160°C, keeping it warm for 2-3 hours, and finally heating it to 180-200°C, keeping it warm for 2-3 hours, and cooling it to room temperature to obtain a phenolic hydroxyl-containing polyetherimide film; S2.3: Dissolve 1-2 parts by weight of the phenolic hydroxyl-containing polyetherimide film in 15-18 parts by weight of N-methylpyrrolidone, then add deionized water to precipitate, wash the precipitate with water until it is neutral, and then dry it to obtain the phenolic hydroxyl-containing polyetherimide.
[0009] Furthermore, the preparation of the polyetherimide membrane in step S3 specifically comprises the following steps: S3.1: adding 2-3 parts by weight of phenolic hydroxyl-containing polyetherimide to 15-20 parts by weight of N,N-dimethylformamide, ultrasonically dispersing for 30-40 minutes, then adding 3-5 parts by weight of titanium-doped benzimidazole-modified metal organic framework, and ultrasonically dispersing for 30-40 minutes to obtain a spinning solution; S3.2: Add the spinning solution into the syringe and spin at 23-25°C to obtain the spinning. The spinning parameters are: voltage 20-25 kV, spinning distance 14-16 cm, spinning rate 1-2 mL / h, receiving roller speed 230-250 r / min to obtain a polyetherimide fiber membrane. Dry the polyetherimide fiber membrane in a vacuum environment at 90-100°C for 1-2 hours to obtain a polyetherimide diaphragm.
[0010] Furthermore, step S4 of preparing core-shell structured nanoparticles specifically comprises the following steps: S4.1: Add 1-2 parts by weight of ammonium formate to 300-350 parts by weight of deionized water, stir to dissolve, add formic acid to adjust the pH to 4.5-4.6, then add 1-2 parts by weight of zirconium dioxide and 3-5 parts by weight of aluminum sulfate 18hydrate, stir in a water bath at 70-75° C. for 6-7 hours to obtain a mixed solution; S4.2: The mixed solution is centrifuged, and the precipitate obtained by centrifugation is washed 5-8 times with deionized water. The washed precipitate is placed in a muffle furnace and heated to 600-650°C at a rate of 10-12°C / min, and calcined for 10-12h to obtain Al2O3@ZrO2 core-shell structured nanoparticles.
[0011] Furthermore, step S5 of preparing barium titanate fibers specifically includes the following steps: S5.1: Dissolve 1-2 parts by weight of barium hydroxide octahydrate in 15-20 parts by weight of acetic acid, stir under a magnetic stirrer for 2-3 hours, then add 4-5 parts by weight of acetylacetone, continue stirring for 10-12 minutes, then add 6-7 parts by weight of tetrabutyl titanate, stir at room temperature for 30-40 minutes, and finally add 0.5-0.6 parts by weight of PVP, stir for 3-4 hours to obtain a barium titanate spinning precursor; S5.2: electrospinning the barium titanate spinning precursor to obtain barium titanate precursor fibers; S5.3: Place the barium titanate precursor fiber in a crucible, calcine it in a muffle furnace at 750-800° C. for 2-3 hours, and then grind it to obtain the barium titanate fiber.
[0012] Furthermore, step S6 of preparing the battery separator specifically comprises the following steps: S6.1: Add 20-23 parts by weight of polyvinylidene fluoride and 1.5-12 parts by weight of a film-forming agent to 50-60 parts by weight of deionized water, stir at 60-90° C. for 20-30 minutes, then add 15-20 parts by weight of barium titanate fibers and 10-12 parts by weight of Al2O3@ZrO2 core-shell structure nanoparticles, stir at 300-500 r / min for 30-40 minutes to obtain a diaphragm coating; S6.2: Apply the separator coating on the surface of the polyetherimide separator, and vacuum dry at 70-80°C for 3-4h to obtain a battery separator.
[0013] Furthermore, the parameters of electrospinning in step S5.2 are: the receiving end rotation speed is set to 120-130 r / min, the distance from the syringe to the receiver is set to 17-18 cm, the voltage is set to 14-16 kV, the push speed is set to 0.1-0.2 mm / min, and the syringe selects a 5 mL syringe.
[0014] Furthermore, in step S6.1, the film-forming agent is nitrile rubber modified epoxy resin, specifically carboxyl-terminated nitrile rubber modified epoxy resin.
[0015] A high temperature resistant battery separator is prepared by any of the above-mentioned methods for preparing a high temperature resistant battery separator.
[0016] Compared with the prior art, the present invention has at least the following beneficial effects: 1. The present invention adopts bis(3-amino-4-hydroxyphenyl)propane containing hydroxyl groups and 4,4-biphenyl ether dianhydride as raw materials to prepare phenolic hydroxyl-containing polyetherimide, and adds titanium-doped benzimidazole-modified metal organic framework to the phenolic hydroxyl-containing polyetherimide to prepare the polyetherimide membrane. By doping titanium in the benzimidazole-modified metal organic framework, the titanium atom can form new chemical bonds with zinc ions in the framework, nitrogen atoms in the benzimidazole and other elements in the organic ligand after being doped into the benzimidazole-modified metal organic framework. The titanium-doped metal organic framework can better resist the influence of high temperature due to its stronger chemical bonds and more stable structure, thereby effectively improving the high temperature resistance of the membrane. In addition, the titanium atom can also coordinate with the phenolic hydroxyl groups in the phenolic hydroxyl-containing polyetherimide to restrict the movement of the molecular chain, thereby increasing the glass transition temperature of the membrane, so that the membrane can still maintain good dimensional stability and mechanical properties at a higher temperature, and is not easy to soften or deform, which helps to improve the performance of the membrane in a high temperature environment.
[0017] 2. The metal organic framework in the present invention has high thermal stability, and its structure can remain relatively stable at high temperatures. When added to the polyetherimide membrane, it can form an interwoven structure with the polyetherimide membrane, which can improve the overall thermal stability and inhibit thermal shrinkage in the membrane. Benzimidazole is a compound with an aromatic ring structure and high thermal stability. After it is modified on the metal organic framework, the framework structure stability of the metal organic framework can be further enhanced. In addition, the metal ions and organic ligands in the titanium-doped benzimidazole-modified metal organic framework can interact with the polyetherimide molecular chains. These interactions enable the polyetherimide membrane to maintain the stability of its shape and size at high temperatures, improve the overall thermal stability of the membrane, and make the membrane less prone to deformation, softening, shrinkage and other problems when the battery works at a higher temperature, thereby ensuring the safety performance and normal operation of the battery. In addition, the metal organic framework has a rich pore structure. After benzimidazole modification, its pore structure is adjusted to make the membrane more conducive to ion transmission, improve the membrane's wetting performance to the electrolyte, and then improve the battery's cycle performance and stability.
[0018] 3. The present invention adds Al2O3@ZrO2 core-shell structure nanoparticles and barium titanate fibers to the diaphragm coating. The synergistic effect of the two can effectively improve the high temperature resistance and puncture strength of the battery diaphragm. The fibrous barium titanate is interwoven with each other in the diaphragm coating to form a network structure. The Al2O3@ZrO2 core-shell structure nanoparticles are filled in the network structure, which can effectively improve the tensile strength, puncture resistance and other mechanical properties of the battery diaphragm. In a high temperature environment, the Al2O3@ZrO2 core-shell structure nanoparticles can effectively disperse heat and reduce local heat concentration, so that the fibrous barium titanate can maintain structural stability, prevent thermal shrinkage and deformation of the diaphragm, reduce the risk of diaphragm damage and battery short circuit due to high temperature, and improve the safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, further serve to explain the principles of the invention and to enable those skilled in the relevant art to make and use the invention.
[0020] Figure 1 A flow chart of a high temperature resistant battery separator and a preparation method thereof used in an embodiment of the present invention. DETAILED DESCRIPTION
[0021] The following is a detailed description of a high temperature resistant battery separator and a preparation method thereof provided by the present invention in combination with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the accompanying drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention.
[0022] The synthesis process of the phenolic hydroxyl-containing polyetherimide in the embodiment is as follows: Example 1
[0023] A method for preparing a high temperature resistant battery separator, such as Figure 1 As shown, the following steps are included: S1: Preparation of titanium-doped benzimidazole-modified metal-organic frameworks S1.1: 2 parts by weight of a mixture of zinc nitrate hexahydrate and 0.05 parts by weight of tetrabutyl titanate are dissolved in 240 parts by weight of methanol, and ultrasonicated for 20 minutes, and then 1 part by weight of 2-methylbenzimidazole is added, and the mixture is stirred and mixed to obtain a mixed solution; S1.2: Add 5 parts by weight of 2-aminobenzimidazole to 50 parts by weight of methanol, stir and dissolve, to obtain a 2-aminobenzimidazole methanol solution; S1.3: Slowly pour 1 part by weight of the mixed solution into 1 part by weight of 2-aminobenzimidazole methanol solution, and react for 4 hours under magnetic stirring, then centrifuge, wash the precipitate twice with methanol, and then dry to obtain a titanium-doped benzimidazole-modified metal organic framework; S2: Preparation of polyetherimide containing phenolic hydroxyl groups S2.1: In a nitrogen atmosphere, 1 part by weight of bis(3-amino-4-hydroxyphenyl)propane and 15 parts by weight of N,N-dimethylacetamide were mixed in an ice bath, and magnetic stirring was performed until they were completely dissolved. Then, 0.4 parts by weight of 4,4-biphenyl ether dianhydride powder was added, and stirring was continued for 20 minutes. Then, 0.4 parts by weight of 4,4-biphenyl ether dianhydride powder was added, and stirring was continued for 20 minutes. Then, 0.4 parts by weight of 4,4-biphenyl ether dianhydride powder was added, and stirring was continued for 5 hours to obtain a viscous polyamic acid solution. S2.2: Casting the viscous polyamic acid solution on a dust-free flat glass, heating it on a heating table, first heating it to 100°C, keeping it warm for 2 hours, then heating it to 150°C, keeping it warm for 2 hours, and finally heating it to 180°C, keeping it warm for 2 hours, cooling it to room temperature, and obtaining a phenolic hydroxyl-containing polyetherimide film; S2.3: dissolving 1 part by weight of a phenolic hydroxyl-containing polyetherimide film in 15 parts by weight of N-methylpyrrolidone, then adding deionized water to precipitate, washing the precipitate with water until it is neutral, and then drying to obtain a phenolic hydroxyl-containing polyetherimide; S3: Preparation of polyetherimide separator S3.1: adding 2 parts by weight of phenolic hydroxyl-containing polyetherimide to 15 parts by weight of N,N-dimethylformamide, ultrasonically dispersing for 30 minutes, then adding 3 parts by weight of titanium-doped benzimidazole-modified metal organic framework, and ultrasonically dispersing for another 30 minutes to obtain a spinning solution; S3.2: adding the spinning solution into a syringe, spinning at 23°C to obtain spinning, the spinning parameters are: voltage 20 kV, spinning distance 14 cm, spinning rate 1 mL / h, receiving roller speed 230 r / min, to obtain a polyetherimide fiber membrane, and drying the polyetherimide fiber membrane under a vacuum environment at 90°C for 1 hour to obtain a polyetherimide separator; S4: Preparation of core-shell nanoparticles S4.1: 1 part by weight of ammonium formate is added to 300 parts by weight of deionized water, stirred to dissolve, and then formic acid is added to adjust the pH to 4.5, and then 1 part by weight of zirconium dioxide and 3 parts by weight of aluminum sulfate 18hydrate are added, and the mixture is stirred in a water bath at 70° C. for 6 hours to obtain a mixed solution; S4.2: The mixed solution was centrifuged, and the precipitate obtained by centrifugation was washed with deionized water for 5 times. The washed precipitate was placed in a muffle furnace and heated to 600°C at a rate of 10°C / min, and calcined for 10 h to obtain Al2O3@ZrO2 core-shell structured nanoparticles; S5: Preparation of barium titanate fibers S5.1: Dissolve 1 part by weight of barium hydroxide octahydrate in 15 parts by weight of acetic acid, stir under a magnetic stirrer for 2 hours, then add 4 parts by weight of acetylacetone, continue stirring for 10 minutes, then add 6 parts by weight of tetrabutyl titanate, stir at room temperature for 30 minutes, and finally add 0.5 parts by weight of PVP, stir for 3 hours to obtain a barium titanate spinning precursor; S5.2: electrospinning the barium titanate spinning precursor to obtain the barium titanate precursor fiber, wherein the electrospinning parameters are: the receiving end rotation speed is set to 120 r / min, the distance from the syringe to the receiver is set to 17 cm, the voltage is set to 14 kV, the push speed is set to 0.1 mm / min, and the syringe is selected to be a 5 mL syringe; S5.3: placing the barium titanate precursor fiber in a crucible, calcining it in a muffle furnace at 750° C. for 2 h, and then grinding it to obtain the barium titanate fiber; S6: Preparation of battery separators S6.1: 20 parts by weight of polyvinylidene fluoride and 1.5 parts by weight of carboxyl-terminated nitrile rubber modified epoxy resin are added to 50 parts by weight of deionized water, and stirred at 60° C. for 20 minutes. Then, 15 parts by weight of barium titanate fibers and 10 parts by weight of Al2O3@ZrO2 core-shell structure nanoparticles are added, and stirred at 300 r / min for 30 minutes to obtain a diaphragm coating; S6.2: Coat the membrane coating on the surface of the polyetherimide membrane and dry it under vacuum at 70° C. for 3 h to obtain a battery membrane. Example 2
[0024] A method for preparing a high temperature resistant battery separator, such as Figure 1 As shown, the following steps are included: S1: Preparation of titanium-doped benzimidazole-modified metal-organic frameworks S1.1: 3 parts by weight of a mixture of zinc nitrate hexahydrate and 0.08 parts by weight of tetrabutyl titanate are dissolved in 250 parts by weight of methanol, and ultrasonicated for 20 minutes, and then 2 parts by weight of 2-methylbenzimidazole are added, and the mixture is stirred and mixed to obtain a mixed solution; S1.2: Add 8 parts by weight of 2-aminobenzimidazole to 60 parts by weight of methanol, stir and dissolve to obtain a 2-aminobenzimidazole methanol solution; S1.3: slowly pour 2 parts by weight of the mixed solution into 2 parts by weight of 2-aminobenzimidazole methanol solution, and react for 4 hours under magnetic stirring, then centrifuge, wash the precipitate twice with methanol, and then dry to obtain a titanium-doped benzimidazole-modified metal organic framework; S2: Preparation of polyetherimide containing phenolic hydroxyl groups S2.1: In a nitrogen atmosphere, 2 parts by weight of bis(3-amino-4-hydroxyphenyl)propane and 18 parts by weight of N,N-dimethylacetamide were mixed in an ice bath, and magnetic stirring was performed until they were completely dissolved. Then, 0.5 parts by weight of 4,4-biphenyl ether dianhydride powder was added, and stirring was continued for 20 minutes. Then, 0.5 parts by weight of 4,4-biphenyl ether dianhydride powder was added, and stirring was continued for 20 minutes. Then, 0.5 parts by weight of 4,4-biphenyl ether dianhydride powder was added, and stirring was continued for 5 hours to obtain a viscous polyamic acid solution. S2.2: Casting the viscous polyamic acid solution on a dust-free flat glass, heating it on a heating table, first heating it to 100°C, keeping it warm for 2 hours, then heating it to 150°C, keeping it warm for 2 hours, and finally heating it to 180°C, keeping it warm for 2 hours, cooling it to room temperature, and obtaining a phenolic hydroxyl-containing polyetherimide film; S2.3: dissolving 2 parts by weight of a phenolic hydroxyl-containing polyetherimide film in 18 parts by weight of N-methylpyrrolidone, then adding deionized water to precipitate, washing the precipitate with water until it is neutral, and then drying to obtain a phenolic hydroxyl-containing polyetherimide; S3: Preparation of polyetherimide separator S3.1: adding 3 parts by weight of phenolic hydroxyl-containing polyetherimide to 20 parts by weight of N,N-dimethylformamide, ultrasonically dispersing for 30 minutes, then adding 5 parts by weight of titanium-doped benzimidazole-modified metal organic framework, and ultrasonically dispersing for another 30 minutes to obtain a spinning solution; S3.2: adding the spinning solution into a syringe, spinning at 23°C to obtain spinning, the spinning parameters are: voltage 20 kV, spinning distance 14 cm, spinning rate 1 mL / h, receiving roller speed 230 r / min, to obtain a polyetherimide fiber membrane, and drying the polyetherimide fiber membrane under a vacuum environment at 90°C for 1 hour to obtain a polyetherimide separator; S4: Preparation of core-shell nanoparticles S4.1: 2 parts by weight of ammonium formate was added to 350 parts by weight of deionized water, stirred to dissolve, and then formic acid was added to adjust the pH to 4.6, and then 2 parts by weight of zirconium dioxide and 5 parts by weight of aluminum sulfate 18hydrate were added, and the mixture was stirred in a water bath at 70° C. for 6 hours to obtain a mixed solution; S4.2: The mixed solution was centrifuged, and the precipitate obtained by centrifugation was washed with deionized water for 5 times. The washed precipitate was placed in a muffle furnace and heated to 600°C at a rate of 10°C / min, and calcined for 10 h to obtain Al2O3@ZrO2 core-shell structured nanoparticles; S5: Preparation of barium titanate fibers S5.1: 2 parts by weight of barium hydroxide octahydrate are dissolved in 20 parts by weight of acetic acid, and stirred under a magnetic stirrer for 2 hours, then 5 parts by weight of acetylacetone are added, and stirring is continued for 10 minutes, and then 7 parts by weight of tetrabutyl titanate are added, and stirring is continued at room temperature for 30 minutes, and finally 0.6 parts by weight of PVP are added, and stirring is continued for 3 hours to obtain a barium titanate spinning precursor; S5.2: electrospinning the barium titanate spinning precursor to obtain the barium titanate precursor fiber, wherein the electrospinning parameters are: the receiving end rotation speed is set to 120 r / min, the distance from the syringe to the receiver is set to 17 cm, the voltage is set to 14 kV, the push speed is set to 0.1 mm / min, and the syringe is selected to be a 5 mL syringe; S5.3: placing the barium titanate precursor fiber in a crucible, calcining it in a muffle furnace at 750° C. for 2 h, and then grinding it to obtain the barium titanate fiber; S6: Preparation of battery separators S6.1: 23 parts by weight of polyvinylidene fluoride and 12 parts by weight of carboxyl-terminated nitrile rubber modified epoxy resin are added to 60 parts by weight of deionized water, and stirred at 90° C. for 30 minutes. Then, 20 parts by weight of barium titanate fibers and 12 parts by weight of Al2O3@ZrO2 core-shell structure nanoparticles are added, and stirred at 500 r / min for 40 minutes to obtain a diaphragm coating; S6.2: Coat the membrane coating on the surface of the polyetherimide membrane and dry it under vacuum at 80° C. for 4 h to obtain a battery membrane. Example 3
[0025] A method for preparing a high temperature resistant battery separator, such as Figure 1 As shown, the following steps are included: S1: Preparation of titanium-doped benzimidazole-modified metal-organic frameworks S1.1: 2 parts by weight of a mixture of zinc nitrate hexahydrate and 0.05 parts by weight of tetrabutyl titanate are dissolved in 240 parts by weight of methanol, and ultrasonicated for 30 minutes, and then 1 part by weight of 2-methylbenzimidazole is added, and the mixture is stirred and mixed to obtain a mixed solution; S1.2: Add 5 parts by weight of 2-aminobenzimidazole to 50 parts by weight of methanol, stir and dissolve, to obtain a 2-aminobenzimidazole methanol solution; S1.3: Slowly pour 1 part by weight of the mixed solution into 1 part by weight of 2-aminobenzimidazole methanol solution, and react for 5 hours under magnetic stirring, then centrifuge, wash the precipitate with methanol three times, and then dry to obtain a titanium-doped benzimidazole-modified metal organic framework; S2: Preparation of polyetherimide containing phenolic hydroxyl groups S2.1: In a nitrogen atmosphere, 1 part by weight of bis(3-amino-4-hydroxyphenyl)propane and 15 parts by weight of N,N-dimethylacetamide were mixed in an ice bath, and magnetic stirring was performed until they were completely dissolved. Then, 0.4 parts by weight of 4,4-biphenyl ether dianhydride powder was added, and stirring was continued for 30 minutes. Then, 0.4 parts by weight of 4,4-biphenyl ether dianhydride powder was added, and stirring was continued for 30 minutes. Then, 0.4 parts by weight of 4,4-biphenyl ether dianhydride powder was added, and stirring was continued for 6 hours to obtain a viscous polyamic acid solution. S2.2: Casting the viscous polyamic acid solution on a dust-free flat glass, heating it on a heating table, first heating it to 120°C, keeping it warm for 3 hours, then heating it to 160°C, keeping it warm for 3 hours, and finally heating it to 200°C, keeping it warm for 3 hours, and cooling it to room temperature to obtain a phenolic hydroxyl-containing polyetherimide film; S2.3: dissolving 1 part by weight of a phenolic hydroxyl-containing polyetherimide film in 15 parts by weight of N-methylpyrrolidone, then adding deionized water to precipitate, washing the precipitate with water until it is neutral, and then drying to obtain a phenolic hydroxyl-containing polyetherimide; S3: Preparation of polyetherimide separator S3.1: adding 2 parts by weight of phenolic hydroxyl-containing polyetherimide to 15 parts by weight of N,N-dimethylformamide, ultrasonically dispersing for 40 minutes, then adding 3 parts by weight of titanium-doped benzimidazole-modified metal organic framework, and ultrasonically dispersing for another 40 minutes to obtain a spinning solution; S3.2: adding the spinning solution into a syringe, spinning at 25°C to obtain spinning, the spinning parameters are: voltage 25 kV, spinning distance 16 cm, spinning rate 2 mL / h, receiving roller speed 250 r / min, to obtain a polyetherimide fiber membrane, and drying the polyetherimide fiber membrane under a vacuum environment at 100°C for 2 h to obtain a polyetherimide separator; S4: Preparation of core-shell nanoparticles S4.1: 1 part by weight of ammonium formate is added to 300 parts by weight of deionized water, stirred to dissolve, and then formic acid is added to adjust the pH to 4.5, and then 1 part by weight of zirconium dioxide and 3 parts by weight of aluminum sulfate 18hydrate are added, and the mixture is stirred in a water bath at 75° C. for 7 hours to obtain a mixed solution; S4.2: The mixed solution was centrifuged, and the precipitate obtained by centrifugation was washed 8 times with deionized water. The washed precipitate was placed in a muffle furnace and heated to 650°C at a rate of 12°C / min, and calcined for 12 h to obtain Al2O3@ZrO2 core-shell structured nanoparticles; S5: Preparation of barium titanate fibers S5.1: Dissolve 1 part by weight of barium hydroxide octahydrate in 15 parts by weight of acetic acid, stir for 3 hours under a magnetic stirrer, then add 4 parts by weight of acetylacetone, continue stirring for 12 minutes, then add 6 parts by weight of tetrabutyl titanate, stir at room temperature for 40 minutes, and finally add 0.5 parts by weight of PVP, stir for 4 hours to obtain a barium titanate spinning precursor; S5.2: electrospinning the barium titanate spinning precursor to obtain the barium titanate precursor fiber, wherein the electrospinning parameters are: the receiving end rotation speed is set to 130 r / min, the distance from the syringe to the receiver is set to 18 cm, the voltage is set to 16 kV, the push speed is set to 0.2 mm / min, and the syringe is selected as a 5 mL syringe; S5.3: placing the barium titanate precursor fiber in a crucible, calcining it in a muffle furnace at 800° C. for 3 h, and then grinding it to obtain the barium titanate fiber; S6: Preparation of battery separators S6.1: 20 parts by weight of polyvinylidene fluoride and 1.5 parts by weight of carboxyl-terminated nitrile rubber modified epoxy resin are added to 50 parts by weight of deionized water, and stirred at 90° C. for 30 minutes. Then, 15 parts by weight of barium titanate fibers and 10 parts by weight of Al2O3@ZrO2 core-shell structure nanoparticles are added, and stirred at 500 r / min for 40 minutes to obtain a diaphragm coating; S6.2: Coat the membrane coating on the surface of the polyetherimide membrane and dry it under vacuum at 80° C. for 4 h to obtain a battery membrane.
[0026] Air permeability test; longitudinal and transverse shrinkage test (heating at 180℃ for 4h, testing the longitudinal and transverse dimensional changes before and after heating); liquid absorption test: soak in electrolyte, take out and weigh after 2h, calculate the liquid absorption according to the weight change before and after; the electrolyte composition is: 1mol / L LiPF6 ethylene carbonate and dimethyl carbonate solution, in which the volume ratio of solvent ethylene carbonate and dimethyl carbonate is 1:1; puncture strength: test according to GB / T10004-2008. Performance test was carried out on Examples 1-3, and the test results are shown in Table 1.
[0027] Table 1. Performance test results of Examples 1-3 Example 1 Example 2 Example 3 Air permeability (sec / 100cc) 153 148 152 Transverse shrinkage (%) 1 1.3 1.1 Longitudinal shrinkage (%) 2.3 2.5 2.4 Puncture strength (gf) 1567 1529 1534 Liquid absorption rate (%) 398 381 387 It can be seen from the data in Table 1 that the battery separators prepared in Examples 1-3 have a lateral shrinkage of 1-1.3% and a longitudinal shrinkage of 2.3-2.5%, indicating that the thermal shrinkage is small at high temperatures, the surface battery separators have excellent high temperature resistance, and the liquid absorption rate is 381-398%, indicating that the battery separators have good wetting ability for the electrolyte, and the battery separators have high strength. This high-strength characteristic helps to improve the overall mechanical stability and safety of the battery and extend the service life of the battery. Therefore, the battery separators prepared by the present invention exhibit excellent comprehensive performance.
[0028] Comparative Example 1 Compared with Example 1, the difference of Comparative Example 1 is that Comparative Example 1 removes the titanium-doped benzimidazole-modified metal organic framework in steps S1 and S3.1, and the remaining steps remain unchanged to prepare the battery separator, which is recorded as Comparative Example 1.
[0029] Comparative Example 2 Compared with Example 1, the difference of Comparative Example 2 is that, in Comparative Example 2, the tetrabutyl titanate in step S1.1 is removed, the benzimidazole-modified metal-organic framework is obtained in step S1.3, and the titanium-doped benzimidazole-modified metal-organic framework in step S3.1 is replaced with an equal weight portion of benzimidazole-modified metal-organic framework, and the remaining steps remain unchanged to prepare the battery separator, which is recorded as Comparative Example 2.
[0030] Comparative Example 3 Compared with Example 1, the difference of Comparative Example 3 is that Comparative Example 3 removes step S1.2, and the mixed solution in S1.3 is directly reacted under magnetic stirring, and the remaining steps remain unchanged to prepare the battery separator, which is recorded as Comparative Example 3.
[0031] The data of Example 1 are used, and performance tests are performed on Comparative Examples 1-3. The test results are shown in Table 2.
[0032] Table 2. Performance test results of comparative examples 1-3 Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Transverse shrinkage (%) 1 4.3 2.2 3.5 Longitudinal shrinkage (%) 2.3 5.9 3.6 4.7 Liquid absorption rate (%) 398 218 389 279 It can be seen from the data in Table 2 that the lateral shrinkage rate and longitudinal shrinkage rate of Comparative Example 2 are both increased compared with those of Example 1, while the liquid absorption rate is decreased, indicating that after the titanium atoms are doped into the benzimidazole-modified metal organic framework, they can better resist the influence of high temperature, thereby effectively improving the high temperature resistance of the diaphragm, so that the diaphragm can still maintain good dimensional stability and mechanical properties at a higher temperature, and is not prone to softening or deformation, which helps to improve the performance of the diaphragm in a high temperature environment; the lateral shrinkage rate and longitudinal shrinkage rate of Comparative Example 3 are also increased compared with Example 1, and the liquid absorption rate is greatly decreased, indicating that after benzimidazole is modified on the metal organic framework, the metal can be further enhanced. The framework structure stability of the organic skeleton improves the overall thermal stability of the diaphragm, so that when the battery works at a higher temperature, the diaphragm is not prone to deformation, softening, shrinkage and other problems, thereby ensuring the safety performance and normal operation of the battery, and adjusting its pore structure after benzimidazole modification to improve the wetting performance of the diaphragm to the electrolyte; the lateral shrinkage rate and longitudinal shrinkage rate of comparative example 1 are higher than those of comparative examples 2-3, and are significantly improved compared with embodiment 1, indicating that the polyetherimide diaphragm prepared by adding titanium-doped benzimidazole-modified metal organic skeleton has better high temperature resistance, and titanium and benzimidazole can produce a synergistic effect, so that the diaphragm prepared therefrom is not easy to shrink at a higher temperature.
[0033] Comparative Example 4 Compared with Example 1, the difference of Comparative Example 4 is that Comparative Example 4 removes the Al2O3@ZrO2 core-shell structure nanoparticles in steps S4 and S6.1, and the remaining steps remain unchanged to prepare the battery separator, which is recorded as Comparative Example 4.
[0034] Comparative Example 5 Compared with Example 1, the difference of Comparative Example 5 is that the barium titanate fibers in steps S5 and S6.1 are removed in Comparative Example 5, and the battery separator is prepared with the remaining steps unchanged, which is recorded as Comparative Example 5.
[0035] The data of Example 1 are used, and performance tests are performed on Comparative Examples 4-5. The test results are shown in Table 3.
[0036] Table 3. Performance test results of comparative examples 4-5 Example 1 Comparative Example 4 Comparative Example 5 Transverse shrinkage (%) 1 2.3 2.6 Longitudinal shrinkage (%) 2.3 3.5 3.7 Puncture strength (gf) 1567 894 872 It can be seen from the data in Table 3 that the addition of both Al2O3@ZrO2 core-shell structured nanoparticles and barium titanate fibers can better improve the high temperature resistance and puncture strength of the battery separator than adding a single component, indicating that the synergistic effect of the two can effectively improve the high temperature resistance and puncture strength of the battery separator.
[0037] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a high temperature resistant battery separator, characterized in that: The steps include: S1: Preparation of titanium-doped benzimidazole-modified metal-organic frameworks Zinc nitrate hexahydrate and 2-methylbenzimidazole are used as raw materials, and tetrabutyl titanate and 2-aminobenzimidazole are added to prepare a titanium-doped benzimidazole-modified metal organic framework; S2: Preparation of polyetherimide containing phenolic hydroxyl groups The polyetherimide containing phenolic hydroxyl group was prepared by using bis(3-amino-4-hydroxyphenyl)propane and 4,4-biphenyl ether dianhydride as raw materials. S3: Preparation of polyetherimide membrane The titanium-doped benzimidazole-modified metal organic framework is added to a solution of phenolic hydroxyl-containing polyetherimide and N,N-dimethylformamide, followed by spinning to obtain a polyetherimide diaphragm; S4: Preparation of core-shell nanoparticles Al2O3@ZrO2 core-shell structure nanoparticles were prepared using zirconium dioxide, aluminum sulfate 18hydrate and ammonium formate as raw materials. S5: Preparation of barium titanate fibers Barium titanate fiber was prepared using barium hydroxide octahydrate, acetic acid and tetrabutyl titanate as raw materials. S6: Preparation of battery separators Barium titanate fibers and Al2O3@ZrO2 core-shell structured nanoparticles were used as additives to prepare a diaphragm coating, and the diaphragm coating was coated on the surface of a polyetherimide diaphragm to prepare a battery diaphragm.
2. The method for preparing a high temperature resistant battery separator according to claim 1, characterized in that: Step S1: Preparation of titanium-doped benzimidazole-modified metal organic framework, specifically comprising the following steps: S1.1: dissolving 2-3 parts by weight of zinc nitrate hexahydrate and 0.05-0.08 parts by weight of tetrabutyl titanate in 240-250 parts by weight of methanol, performing ultrasonication for 20-30 minutes, then adding 1-2 parts by weight of 2-methylbenzimidazole, stirring and mixing to obtain a mixed solution; S1.2: Add 5-8 parts by weight of 2-aminobenzimidazole to 50-60 parts by weight of methanol, stir and dissolve to obtain a 2-aminobenzimidazole methanol solution; S1.3: Slowly pour 1-2 parts by weight of the mixed solution into 1-2 parts by weight of 2-aminobenzimidazole methanol solution, and react for 4-5 hours under magnetic stirring, then centrifuge, wash the precipitate with methanol 2-3 times, and then dry to obtain a titanium-doped benzimidazole-modified metal organic framework.
3. The method for preparing a high temperature resistant battery separator according to claim 2, characterized in that: Step S2: Preparation of phenolic hydroxyl-containing polyetherimide, specifically comprising the following steps: S2.1: In a nitrogen atmosphere, 1-2 parts by weight of bis(3-amino-4-hydroxyphenyl)propane and 15-18 parts by weight of N,N-dimethylacetamide are mixed in an ice bath, and magnetic stirring is performed until they are completely dissolved, and then 0.4-0.5 parts by weight of 4,4-biphenyl ether dianhydride powder is added, and stirring is continued for 20-30 minutes, and then 0.4-0.5 parts by weight of 4,4-biphenyl ether dianhydride powder is added, and stirring is continued for 20-30 minutes, and then 0.4-0.5 parts by weight of 4,4-biphenyl ether dianhydride powder is added, and stirring is continued for 5-6 hours to obtain a viscous polyamic acid solution; S2.2: Casting the viscous polyamic acid solution on a dust-free flat glass, heating it on a heating table, first heating it to 100-120°C, keeping it warm for 2-3 hours, then heating it to 150-160°C, keeping it warm for 2-3 hours, and finally heating it to 180-200°C, keeping it warm for 2-3 hours, and cooling it to room temperature to obtain a phenolic hydroxyl-containing polyetherimide film; S2.3: Dissolve 1-2 parts by weight of the phenolic hydroxyl-containing polyetherimide film in 15-18 parts by weight of N-methylpyrrolidone, then add deionized water to precipitate, wash the precipitate with water until it is neutral, and then dry it to obtain the phenolic hydroxyl-containing polyetherimide.
4. The method for preparing a high temperature resistant battery separator according to claim 3, characterized in that: Step S3: Preparation of polyetherimide diaphragm, specifically comprising the following steps: S3.1: adding 2-3 parts by weight of phenolic hydroxyl-containing polyetherimide to 15-20 parts by weight of N,N-dimethylformamide, ultrasonically dispersing for 30-40 minutes, then adding 3-5 parts by weight of titanium-doped benzimidazole-modified metal organic framework, and ultrasonically dispersing for 30-40 minutes to obtain a spinning solution; S3.2: Add the spinning solution into the syringe and spin at 23-25°C to obtain the spinning. The spinning parameters are: voltage 20-25 kV, spinning distance 14-16 cm, spinning rate 1-2 mL / h, receiving roller speed 230-250 r / min to obtain a polyetherimide fiber membrane. Dry the polyetherimide fiber membrane in a vacuum environment at 90-100°C for 1-2 hours to obtain a polyetherimide diaphragm.
5. The method for preparing a high temperature resistant battery separator according to claim 4, characterized in that: Step S4: Preparation of core-shell structured nanoparticles, specifically comprising the following steps: S4.1: Add 1-2 parts by weight of ammonium formate to 300-350 parts by weight of deionized water, stir to dissolve, add formic acid to adjust the pH to 4.5-4.6, then add 1-2 parts by weight of zirconium dioxide and 3-5 parts by weight of aluminum sulfate 18hydrate, stir in a water bath at 70-75° C. for 6-7 hours to obtain a mixed solution; S4.2: The mixed solution is centrifuged, and the precipitate obtained by centrifugation is washed 5-8 times with deionized water. The washed precipitate is placed in a muffle furnace and heated to 600-650°C at a rate of 10-12°C / min, and calcined for 10-12h to obtain Al2O3@ZrO2 core-shell structured nanoparticles.
6. The method for preparing a high temperature resistant battery separator according to claim 5, characterized in that: Step S5: Preparation of barium titanate fiber, specifically comprising the following steps: S5.1: Dissolve 1-2 parts by weight of barium hydroxide octahydrate in 15-20 parts by weight of acetic acid, stir under a magnetic stirrer for 2-3 hours, then add 4-5 parts by weight of acetylacetone, continue stirring for 10-12 minutes, then add 6-7 parts by weight of tetrabutyl titanate, stir at room temperature for 30-40 minutes, and finally add 0.5-0.6 parts by weight of PVP, stir for 3-4 hours to obtain a barium titanate spinning precursor; S5.2: electrospinning the barium titanate spinning precursor to obtain barium titanate precursor fibers; S5.3: Place the barium titanate precursor fiber in a crucible, calcine it in a muffle furnace at 750-800° C. for 2-3 hours, and then grind it to obtain the barium titanate fiber.
7. The method for preparing a high temperature resistant battery separator according to claim 6, characterized in that: Step S6: Preparation of battery separator, specifically comprising the following steps: S6.1: Add 20-23 parts by weight of polyvinylidene fluoride and 1.5-12 parts by weight of a film-forming agent to 50-60 parts by weight of deionized water, stir at 60-90° C. for 20-30 minutes, then add 15-20 parts by weight of barium titanate fibers and 10-12 parts by weight of Al2O3@ZrO2 core-shell structure nanoparticles, stir at 300-500 r / min for 30-40 minutes to obtain a diaphragm coating; S6.2: Coat the membrane coating on the surface of the polyetherimide membrane, and vacuum dry at 70-80° C. for 3-4 hours to obtain a battery membrane.
8. The method for preparing a high temperature resistant battery separator according to claim 4, characterized in that: The parameters of electrospinning in step S5.2 are: the receiving end rotation speed is set to 120-130 r / min, the distance from the syringe to the receiver is set to 17-18 cm, the voltage is set to 14-16 kV, the push speed is set to 0.1-0.2 mm / min, and the syringe is selected as a 5 mL syringe.
9. The method for preparing a high temperature resistant battery separator according to claim 6, characterized in that: In step S6.1, the film-forming agent is nitrile rubber modified epoxy resin, specifically carboxyl-terminated nitrile rubber modified epoxy resin.
10. A high temperature resistant battery separator, characterized in that: It is prepared by the method for preparing a high temperature resistant battery separator according to any one of claims 1 to 9.
Citation Information
Patent Citations
Organometallic framework polyrotaxane type diaphragm and application thereof in battery
CN111276662A
Ultrathin coated diaphragm and preparation method thereof
CN114709566A
Inorganic matter doped polybenzimidazole high-temperature proton exchange membrane as well as preparation method and application thereof
CN116779924A
High-temperature energy storage hybrid polyetherimide dielectric thin film, preparation method therefor, and use thereof
US20230323032A1